Integration of Building Information Modeling (BIM) and LEED for A Green Building Rating - Rahman, Mizanoor; Mim, Sohana Alam; Oshin, Shamanta Azad (Journal of Engineering Science, 2021)
Green building design and construction is a global demand to save this earth. Leadership in Energy and Environmental Design (LEED) is the world's most widely implemented sustainable building rating system. Building Information Modeling (BIM) technology assist to keep multi-disciplinary information into a single model, and it provides an ability to perform this research. The aim is to assess the pre-certification of a proposed residential building project in integration with BIM and LEED and find out the impact of cost for a green building project. A Prototype 3D model was developed by BIM technology for the LEED certification process. A total of 704 simulations was conducted by using Green Building Studio (GBS) tools. All simulation results were calculated based on nine categories of the LEED rating system. The results of this study indicate that the lifecycle cost can be reduced significantly for a high-performance green building despite of having a high initial investment cost. Journal of Engineering Science 12(2), 2021, 47-57